The effects of togu-jumper use on core muscle activity during plank exercise - Hae-Seong Moon; Woen-Sik Chae; Jae-Hu Jung (Korea Institute of Sport Science, 2020)
Purpose This study was to analyze and compare series of muscle activities during plank exercises with use of togu-jumper. Methods Ten male subjects (age 26.9±1.7 yrs, height 172.2±5.7 cm, weight 66.5±7.5 kg) who have no musculoskeletal disorder with one's upper or lower limb were selected as subjects. To analyze and compare series of muscle activity, five of surface EMG electrodes were attached to the upper rectus abdominis (URA), lower rectus abdominis (LRA), external abdominal oblique (EO), erector spinae (ES) and gluteus maximus (GM). Each subject did plank exercise on stable support surfaces (normal surfaces) and unstable support surfaces with the togu-jumper. For each dependent variable, one-way ANOVA with repeated measures were performed with significance level p<.05. Contrasts were performed to execute post tests for results with statistical significance. Results The study showed that the average IEMG values of URA and LRA increased in Upper (Togu-jumper used upper limb) compared to normal surfaces. This is perhaps because the effects of URA more than any other muscles for body stability. Furthermore, the peak IEMG values of LRA increased in Upper and Lower (Togu-jumper used lower limb) compared to normal surfaces. In addition, peak IEMG values of EO increased in Upper compared to Normal. This may have resulted due to momentary strong muscle activity in LRA and EO to correct body posture and balance. Therefore, using Togu-jumper on upper limb maximizes the performance of core training in plank exercise. Conclusions The study may be further applied to a method for effective training. It is considered that research and analysis has to be further done on modified plank exercise. Additionally, it is necessary to analyze not only global muscle but also local muscle, as a comprehensive research, to suggest ideal method for plank exercise.